Gerakan Ekofeminisme Dalam Pemberdayaan Perempuan Pengolah Limbah (Studi Kasus Komunitas Pengolah Limbah di Desa Narmada) - Ika Wijayanti; Nila Kusuma; Oryza Pneumatica (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2019)
Research titled "Ecofeminism Movement in Women Empowerment Waste processors (case study of waste processing community in Narmada village)" is taking location in Narmada village, Narmada District, West Lombok Regency. By doing this research is expected that researchers are able to: (1) know deeply the meaning of ekofemism to Uncle Sam's garbage Processing community, (2) Know the principles of ecofeminism developed in waste management activities/ Waste in the Uncle Sam community, (3) Knowing the obstacles facing women in the implementation of waste processing. The study uses an exploratoryqualitative research method. The subject of this study was the female member of Uncle Sam's community. Data is collected through interviews and observations to compile information on ecofeminism, ecofeminism principles developed in waste management activities in the Uncle Sam community, and the constraints faced Women in the conduct of waste processing. Further data is analyzed by conducting several phases including data collection, data classification, interpretation, and research report writing. The results of this study show that (i) women in the Uncle Sam community suggest that Ecofeminism is one of the steps to save the environment can be styled by members of Uncle Sam's community. (ii) Principles of ecofeminism that Developed by the Uncle Sam community, among others, maintaining the integrity of the biosphere, living in harmony with nature, equal relationships, versatility, caring and compassion. In addition, the principle of democracy was developed related to the activities of the Uncle Sam community. (iii) The obstacles facing women Uncle Sam Community is integrating the activities of Uncle Sam's community with other village organizations, the difficult Invites other citizens to participate in the processing of waste, as well as changing the community's mindset about the economical value of waste/waste.